Endoscopic treatment of biliary fistulas: results of 20 patients - Fatih HİLMİOĞLU,; Bülent YILDIRIM,; Melih KARINCAOĞLU,; Murat ALADAĞ,; Bülent KANTARÇEKEN,; İbrahim DOĞAN, (Turkish Journal of Gastroenterology, 2019)
-